NCM positive electrode particle coated with LLZO and glass phase
By covering the glass phase and LLZO fine particles on the surface of the NCM positive electrode particles and covering them with nano-carbon tubes to form a composite structure, the problems of interfacial side reactions and low conductivity are solved, and the pathway and electron conductivity of lithium ions are improved. Extend battery life and reduce cobalt usage.
Patent Information
- Application Number
- CN202411356047.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-06-05
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
The existing positive electrode conductive units are prone to side reactions at the interface in the battery, resulting in a decrease in service life and low electron conductivity, affecting the overall battery performance.
The surface of the NCM positive electrode particles is coated with glass phase material and coated with LLZO fine particles and nanocarbon tubes to form a composite structure to reduce interface impedance and improve conductivity.
Effectively prevent interface side reactions, improve the pathway and electron conductivity of lithium ions, extend battery life, improve rate charging and discharging performance, and reduce cobalt usage.
Smart Images

Figure CN119252890A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of positive electrode materials, and in particular to NCM positive electrode particles coated with LLZO and a glass phase. Background Art
[0002] The battery is mainly formed by placing the positive electrode and the negative electrode in the electrolyte. The positive electrode is a large number of positive electrode conductive units (positive electrode materials, such as lithium cobalt oxide) mixed and dispersed in the slurry. Generally speaking, the positive electrode conductive unit must be mixed with the conductive slurry before it can be applied to the electrode sheet and assembled into a battery. Therefore, the numerous positive electrode conductive units (positive electrode materials) are connected to each other through the conductive slurry. Therefore, the conductive slurry must have conductive properties or conductivity, so that free electrons can migrate in different positive electrode conductive units without consuming too much energy due to internal resistance, and achieve effective conduction. Therefore, when manufacturing the slurry, it is necessary to consider the use of specific conductive materials to adjust the conductivity of the slurry.
[0003] Generally, in order to increase the conductivity, a plurality of positive electrode particles are filled in the positive electrode slurry, wherein the material of the positive electrode particles can be selected from NCM (lithium nickel cobalt manganese oxide), LMFP (lithium iron manganese phosphate), etc. or a mixture thereof, and the positive electrode particles are distributed in the positive electrode slurry. However, the interface of the positive electrode particles in the conventional technology is prone to side reactions, which reduces the service life of the positive electrode, and the electronic conductivity is low, so the overall battery performance is poor.
[0004] Based on the long-term experience in battery materials, the applicant hopes to propose a new design. In order to further increase the conductivity of the entire slurry, carbon nanotubes and nano-scale amorphous carbon are added to coat the positive electrode particles in the positive electrode material of the battery to improve the conductivity of the entire positive electrode. In addition, the glass phase material is coated on the surface of the positive electrode particles, thereby reducing the interface impedance; improving the powder coating and stabilizing it in the electrolyte to prevent interface side reactions.
[0005] Therefore, the prior art has defects and needs to be improved. Summary of the invention
[0006] The purpose of the present invention is to solve the problems in the above-mentioned known technologies. The present invention proposes a NCM positive electrode particle coated with LLZO and a glass phase, wherein a glass phase material is coated on the surface of the NCM large particle to form the glass phase layer, wherein the glass phase layer can prevent the direct contact between the NCM large particle and the electrolyte, and reduce the interface side reaction; at the same time, the interface impedance of lithium ions entering and exiting the NCM large particle is reduced, the rate charge and discharge performance is improved, and the volume change of the charge and discharge is accommodated, the mechanical properties of the powder are improved, and the breakage is reduced. The NCM large particle is coated with a large number of LLZO fine particles. The LLZO (lithium lanthanum zirconium oxide) fine particles have the ability to accommodate and evenly flow lithium ions. Therefore, when lithium ions pass through the positive electrode, the path of lithium ions can be dispersed by guiding the dispersed LLZO fine particles, so the design of the positive electrode of the present invention can make lithium ions have a better path. The present invention also coats the outer side of the NCM large particle coated with LLZO fine particles with nano-carbon tubes and the nano-scale amorphous carbon. The electrons can be conducted on the composite NCM large particles and the nano-scale amorphous carbon can fill the gaps formed by the multiple carbon nanotubes, forming a more complete electron conduction path. The structure of the present invention can provide stability for the overall positive electrode slurry structure, so the amount of cobalt used can be reduced.
[0007] To achieve the above-mentioned object, the present invention proposes a NCM positive electrode particle coated with LLZO and a glass phase, which is present in the positive electrode slurry layer of the positive electrode of a solid-state or quasi-solid-state battery, and each of the NCM positive electrode particles coated with LLZO and a glass phase comprises: a large NCM (nickel cobalt manganese oxide) particle; the large NCM particle is in an irregular cubic shape; the outside of the large NCM particle has a glass phase layer that partially or completely covers the surface of the large NCM particle; wherein the glass phase layer is used to prevent direct contact between the electrolyte and the positive electrode material; and reduce the interface impedance of lithium ions entering and exiting, improve the rate charge and discharge performance and the glass phase layer. The existence of the glassy phase layer can accommodate the volume changes caused by charging and discharging; there are numerous LLZO (lithium lanthanum zirconium oxide) fine particles; the LLZO fine particles are distributed in the glassy phase layer or on the surface of the glassy phase layer, and as a whole form a composite NCM large particle; wherein the multiple LLZO fine particles are attached inside and outside the glassy phase layer on the outer surface of the NCM large particle, and the ion conduction ability of the LLZO fine particles for lithium ions is much higher than that of the NCM large particles, and no side reactions are produced with the lithium ions; therefore, when lithium ions pass through the positive electrode, the pathway of the lithium ions can be dispersed with the help of the guidance of the dispersed LLZO fine particles.
[0008] The NCM positive electrode particles of the present invention further include: a plurality of CNTs (carbon nanotubes) are coated on the periphery of the composite NCM large particles; so the CNTs are entirely coated on the composite NCM large particles, and the entirety forms a positive electrode particle wrapped with CNTs. The CNTs are short-chain CNTs and long-chain CNTs, the short-chain CNTs are between 0.5 microns and 1 micron in length, and the long-chain CNTs are between 3 microns and 8 microns in length; the short-chain CNTs are used to bridge the LLZO fine particles and the NCM large particles; the long-chain CNTs are entirely coated on the composite NCM large particles, so that the entire composite NCM large particles have better conductivity.
[0009] The NCM positive electrode particles of the present invention further include: a plurality of nano-scale amorphous carbons are coated on the outside of the positive electrode particles wrapped with CNTs, forming a carbon-coated positive electrode particle as a whole, and each of the nano-scale amorphous carbons is mainly located between the gaps formed by the interlacing of the plurality of CNTs.
[0010] The features and advantages of the present invention may be further understood from the following description, which is to be read with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 A diagram showing the structure of the positive electrode particles of the present invention.
[0012] Figure 2 A structural diagram showing the positive electrode of the present invention.
[0013] Figure 3 A structural diagram showing the composite NCM large particles of the present invention.
[0014] Figure 4 A structural diagram showing the composite NCM large particles of the present invention.
[0015] Figure 5 A structural diagram showing the composite NCM large particles of the present invention. DETAILED DESCRIPTION
[0016] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0017] The structural composition of the present invention, as well as the effects and advantages it can produce, are described in detail below with reference to a preferred embodiment of the present invention.
[0018] Please refer to Figures 1 to 5 As shown, the NCM positive electrode particles coated with LLZO and glass phase of the present invention are shown, and the structure is explained as follows.
[0019] like Figure 2 As shown, a positive electrode 100 of a general solid-state or quasi-solid-state battery comprises:
[0020] a positive electrode substrate 10;
[0021] A positive electrode slurry layer 12 is coated on the positive electrode substrate 10, wherein the positive electrode slurry layer 12 comprises:
[0022] A positive electrode slurry 14 containing a binder, and
[0023] A plurality of positive electrode particles 200 are distributed in the positive electrode slurry 14.
[0024] Each of the positive electrode particles 200 comprises:
[0025] A NCM (nickel cobalt manganese oxide) large particle 22, the size of the NCM large particle 22 is 3 microns to 5 microns; it is a single crystal structure. Figure 1 As shown, the NCM large particles 22 are in an irregular cubic shape. The total weight of the plurality of positive electrode particles 200 accounts for 80 wt% to 98 wt% of the positive electrode slurry layer 12 .
[0026] The NCM large particle 22 has a glass phase layer 25 covering the surface of the NCM large particle 22 (preferably completely covering the surface) (e.g. Figure 3 ), the whole forms a NCM large particle 250 having a glass phase layer. The material of the glass phase layer 25 is a lithium ion conductivity higher than 10 -5 S / cm non-crystalline oxide or non-oxide solid electrolyte. For example: lithium and IIIA, IVA, VA group oxides (such as: Li2O-RO x , R=B (boron), Al (aluminum), Si (silicon), Ge (germanium), P (phosphorus), As (arsenic), etc., x=1~3), or lithium halide / halogen-oxide (such as Li-MO, where M is at least one of the halogens F (fluorine), Cl (chlorine), Br (bromine), I (iodine)), or lithium-sulfide (such as: Li2S-P2S5), or amorphous oxide-based solid electrolyte (such as amorphous perovskite-based solid electrolyte (LLTO), garnet-based solid electrolyte (LLZO), or lithium-phosphorus-oxygen-nitride (LiPON) at least one.
[0027] The glass phase layer 25 has a thickness ranging from 5 nanometers to 100 nanometers.
[0028] The glass phase layer can prevent the direct contact between the large NCM particles and the electrolyte, reducing the interface side reactions; at the same time, it can reduce the interface impedance of lithium ions entering and exiting the large NCM particles, improve the rate charge and discharge performance, and the existence of the glass phase layer 25 can accommodate the volume changes during charge and discharge, improve the mechanical properties of the powder, and reduce breakage.
[0029] There are numerous LLZO (lithium lanthanum zirconium oxide) fine particles 24, which are distributed in the glass phase layer 25 or on the surface of the glass phase layer 25, and the whole forms a composite NCM large particle 20. 6.2 Ga 0.8 La3Zr2O 12 (Gadium-doped lithium lanthanum zirconium oxide compound), the gallium doping can also be changed to aluminum (Al) doping or barium (Ba) doping, etc. The lateral dimension of the LLZO fine particle 24 (i.e. the dimension along the spherical surface of the LLZO fine particle) is between 50 nanometers and 300 nanometers; basically, after sintering, the longitudinal dimension of the LLZO fine particle 24 along the radial direction of the sphere becomes shorter, the lateral dimension becomes wider, and the total volume remains unchanged. In a single NCM positive electrode particle covered with the LLZO fine particle 24 and the glass phase layer 25 (i.e. the composite NCM large particle 20), the ratio of the total weight of all the LLZO fine particles 24 to the weight of the NCM large particle 250 with the glass phase layer is between 0.2wt% and 2wt%.
[0030] In the present invention, the plurality of LLZO fine particles 24 are attached inside and outside the glass phase layer 25 on the outer surface of the NCM large particle 22, because the ion guiding ability of the LLZO fine particles 24 for lithium ions is much higher than that of the NCM large particle 22, and no side reaction occurs with the lithium ions. Therefore, when lithium ions pass through the positive electrode 100, the path of lithium ions can be dispersed with the guidance of the dispersed LLZO fine particles 24, so the design of the present invention can make lithium ions have a better path, greatly increase the efficiency of the overall battery, and no side reaction occurs, so the service life of the entire battery can be extended.
[0031] The LLZO in the LLZO fine particles 24 is preferably selected from at least one of Ga-LLZO (gallium-doped lithium lanthanum zirconium oxide), Cu-LLZO (copper-doped lithium lanthanum zirconium oxide), Ta-LLZO (tantalum-doped lithium lanthanum zirconium oxide), Sr-LLZO (strontium-doped lithium lanthanum zirconium oxide) and Al-LLZO (aluminum-doped lithium lanthanum zirconium oxide).
[0032] More preferably, the LLZO is selected from Cu a X b-LLZO (copper-doped lithium lanthanum zirconium oxide), X is selected from at least one of Ga (gallium), Ta (tantalum), Sr (strontium), Ba (barium), Al (aluminum), where a+b = 0.25-0.8, a>0.1; the technology of using copper doping in LLZO is quite difficult, but it can make the overall structure more stable, the passage of lithium ions can be smoother, and the sintering speed is increased and the manufacturing cost is relatively cheap. And when the material is exposed to air, the formation of lithium carbonate is reduced. That is, the surface stability of the entire material during sintering is increased.
[0033] The LLZO fine particles 24 and the NCM large particles 22 in the present invention are both crystalline structures, so they have good overall stability and will not be easily released or dissociated, so the voltage of the entire battery can be increased.
[0034] like Figure 4 and Figure 5 As shown, the present invention also includes:
[0035] A plurality of CNTs 30 (ie, carbon nanotubes 30) are coated on the periphery of the composite NCM large particle 20. Therefore, the CNTs 30 completely coat the composite NCM large particle 20 to form a positive electrode particle 300 (eg, Figure 5 ).
[0036] In the present invention, the CNT 30 is short-chain CNT 32 and long-chain CNT 34, wherein the length of the short-chain CNT 32 is between 0.5 microns and 1 micron, and the length of the long-chain CNT 34 is between 3 microns and 8 microns. The total weight of the CNT 30 accounts for 0.1 wt% to 2 wt% of the weight of the single composite NCM large particle 20.
[0037] like Figure 1 As shown, the short-chain CNT 32 is used to bridge the LLZO fine particles 24 and the NCM large particles 22 (as shown in FIG. Figure 4 The long-chain CNT 34 is used as a whole to cover the composite NCM large particle 20 (such as Figure 1 ), so that the entire composite NCM large particle 20 has good conductivity. CNT is a very good conductive material, which helps the electronic conduction of the entire positive electrode material; on the other hand, the LLZO fine particle 24 helps the conduction of lithium ions.
[0038] The carbon nanotubes 30 (i.e., CNT 30) are used to increase the electronic conductivity, that is, to form a conductive bridge between the various LLZO fine particles, so that the electrons can be conducted on the composite NCM large particles 20. Because the carbon nanotubes have extremely high conductivity, the electrons can be conducted between the different LLZO fine particles 24 and the NCM large particles 22 through the carbon nanotubes 30, so the conductivity of the entire positive electrode is increased as a whole. The carbon nanotubes 30 can form different levels of cross-connections on the LLZO fine particles 24 and the NCM large particles 22. When more carbon nanotubes 30 are added, the conductivity of the entire positive electrode 100 will be improved.
[0039] The advantage of using carbon nanotubes in the present invention is that lithium ions can be easily stabilized between the carbon nanotubes, so the positive electrode slurry in the present invention can stabilize a large number of lithium ions, thereby improving the overall conductivity of lithium ions, and electrons can be easily fixed between the short-chain and long-chain carbon nanotubes, thereby improving the overall conductivity of lithium ions. In addition, because the ion conductivity is very high, it helps the rapid charging and rapid discharging of the entire battery, and can also reduce the use of cobalt, thereby reducing the overall production cost.
[0040] A plurality of nano-scale amorphous carbons 35 are coated on the outside of the positive electrode particles 300 wrapped with CNTs, forming a carbon-coated positive electrode particle 350 as a whole. Each of the nano-scale amorphous carbons 35 is mainly located between the gaps formed by the interlacing of the plurality of CNTs 30. The nano-scale amorphous carbons 35 are like super P conductive agents. The size of the nano-scale amorphous carbons 35 is 20 nanometers to 100 nanometers. The total weight of the nano-scale amorphous carbons 35 accounts for a proportion of 0.1wt% to 2wt% of the weight of a single composite NCM large particle 20. The nano-scale amorphous carbons 35 are conductive agents like the CNTs 30. Because the nano-scale amorphous carbon 35 is in the form of particles, and the nano-carbon tubes 30 are in the form of long strips, gaps are formed between the criss-crossed nano-carbon tubes 30, and these gaps cannot conduct current. Therefore, adding the nano-scale amorphous carbon 35 to the gaps can allow the charge to be conducted to the next nano-carbon tube 30 through the bridging of the nano-scale amorphous carbon 35, thereby further increasing the current transfer.
[0041] In the present invention, (the CNT 30+the nanometer-scale amorphous carbon 35):single composite NCM large particle 20=(0.09-3):100 (weight ratio).
[0042] The ratio of the CNT 30 : the nano-scale amorphous carbon 35 : the composite NCM large particle 20 (including the LLZO fine particle 24 and the NCM large particle with a glass phase layer) is 0.5:1:100 (by weight).
[0043] The above structure can make the positive electrode 100 bear more lithium ions, so the whole positive electrode 100 can bear a higher voltage. For example, for a battery with an original voltage of 4.3V, the voltage can be increased from 4.3V to 4.5V by using the design of the present invention.
[0044] The advantage of the present invention is that the glass phase material is coated on the surface of the NCM large particles to form the glass phase layer, wherein the glass phase layer can prevent the direct contact between the NCM large particles and the electrolyte, reduce the interface side reaction; at the same time, reduce the interface impedance of lithium ions entering and leaving the NCM large particles; improve the rate charge and discharge performance and accommodate the volume change of charge and discharge, improve the mechanical properties of the powder, and reduce breakage. The NCM large particles are coated with a large number of LLZO fine particles. The LLZO fine particles have the ability to accommodate and evenly flow lithium ions. Therefore, when lithium ions pass through the positive electrode, the path of lithium ions can be dispersed with the guidance of the dispersed LLZO fine particles, so the design of the positive electrode of the present invention can make lithium ions have a better path. The present invention also coats the outer surface of the NCM large particles coated with LLZO fine particles with nano-carbon tubes and the nano-scale amorphous carbon. It allows electrons to be conducted on the composite NCM large particles and each of the nano-scale amorphous carbons can be filled in the gaps formed by the interlacing of the multiple nano-carbon tubes to form a more complete electron conduction path. The structure of the present invention can provide stability for the overall positive electrode slurry structure, thereby reducing the amount of cobalt used.
[0045] In summary, the humanized and considerate design of the present invention is quite in line with the actual needs. It specifically improves the existing deficiencies and has obvious breakthrough advantages compared with the known technology. It does have the improvement of efficacy and is not easy to achieve. The present invention has not been published or disclosed in domestic and foreign literature and markets, and has complied with the provisions of the Patent Law.
[0046] The above detailed description is a specific description of a feasible embodiment of the present invention, but the embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the technical spirit of the present invention should be included in the patent scope of the present invention.
Claims
1. A NCM positive electrode particle coated with LLZO and a glass phase, wherein the positive electrode particle is present in a positive electrode slurry layer of a positive electrode of a solid-state or quasi-solid-state battery, and each of the NCM positive electrode particles coated with LLZO and a glass phase comprises: A NCM large particle; the NCM large particle is in an irregular cubic shape; the NCM large particle has a glass phase layer on the outside, which partially or completely covers the surface of the NCM large particle; The overall formation of NCM large particles with glass phase layer; The glass phase layer can prevent the direct contact between the NCM large particles and the electrolyte, reduce the interface side reaction; and at the same time reduce the interface impedance of lithium ions entering and leaving the NCM large particles; There are numerous LLZO fine particles; the LLZO fine particles are distributed in the glass phase layer or on the surface of the glass phase layer, and the whole forms a composite NCM large particle; wherein a plurality of the LLZO fine particles are attached inside and outside the glass phase layer on the outer surface of the NCM large particle, and the ion conduction ability of the LLZO fine particles for lithium ions is much higher than that of the NCM large particles, and no side reaction occurs with lithium ions; therefore, when lithium ions pass through the positive electrode, the pathway of lithium ions can be dispersed with the help of the guidance of the dispersed LLZO fine particles.
2. The NCM positive electrode particle coated with LLZO and glass phase according to claim 1, characterized in that: The NCM large particle size is 3 microns to 5 microns; it is a single crystal structure; and the glass phase layer thickness is between 5 nanometers and 100 nanometers.
3. The NCM positive electrode particle coated with LLZO and glass phase according to claim 1, characterized in that: The glass phase layer is made of a material having a lithium ion conductivity higher than 10 -5 S / cm non-crystalline oxide or non-oxide solid electrolyte; it is selected from at least one of lithium halides / halogen-oxides, lithium and IIIA, IVA, VA group oxides, amorphous oxide-based solid electrolytes, amorphous perovskite-based solid electrolytes, garnet-based solid electrolytes, lithium-phosphorus-oxygen-nitride, and lithium-sulfide.
4. The NCM positive electrode particle coated with LLZO and glass phase according to claim 1, characterized in that: The glass phase layer is made of a material having a lithium ion conductivity higher than 10 -5 S / cm non-crystalline oxide or non-oxide solid electrolyte; which is selected from Li-MO, wherein M is at least one of the halogens selected from the group consisting of fluorine, chlorine, bromine and iodine; Li2O-RO x , wherein R = at least one of boron, aluminum, silicon, germanium, phosphorus, and arsenic, and x = 1 to 3; Li-La-Ti-O; Li-La-Zr-O; LIPON; Li2S-P2S5; At least one of the above.
5. The NCM positive electrode particle coated with LLZO and glass phase according to claim 1, characterized in that: The LLZO in the LLZO fine particles is selected from at least one of gallium-doped lithium lanthanum zirconium oxide compounds, copper-doped lithium lanthanum zirconium oxide compounds, tantalum-doped lithium lanthanum zirconium oxide compounds, strontium-doped lithium lanthanum zirconium oxide compounds, barium-doped lithium lanthanum zirconium oxide compounds and aluminum-doped lithium lanthanum zirconium oxide compounds.
6. The NCM positive electrode particle coated with LLZO and glass phase according to claim 1, characterized in that: The LLZO in the LLZO fine particles is selected from Cu a X b -LLZO, i.e. copper-doped lithium lanthanum zirconium oxide, X is selected from at least one of gallium, tantalum, strontium, barium and aluminum, wherein a+b=0.25-0.8, a>0.1; doping LLZO with copper can make the overall structure more stable, the passage of lithium ions can be smoother, and the sintering speed is increased with relatively low manufacturing cost; and when the material is exposed to air, the formation of lithium carbonate is reduced; that is, the surface stability of the entire material during sintering is increased.
7. The NCM positive electrode particle coated with LLZO and glass phase according to claim 1, characterized in that: The lateral dimension of the LLZO fine particle, ie, the dimension along the spherical surface of the LLZO fine particle, is between 50 nanometers and 300 nanometers.
8. The NCM positive electrode particle coated with LLZO and glass phase according to claim 1, characterized in that: In a single NCM positive electrode particle coated with LLZO and a glass phase, the ratio of the total weight of all the LLZO fine particles to the weight of the NCM large particle with a glass phase layer is between 0.2wt% and 2wt%.
9. The NCM positive electrode particle coated with LLZO and glass phase according to claim 1, characterized in that: It also includes: a plurality of CNTs are coated on the periphery of the composite NCM large particle; so the CNTs entirely coat the composite NCM large particle, and the entirety forms a positive electrode particle wrapped with the CNTs.
10. The NCM positive electrode particle coated with LLZO and glass phase according to claim 9, characterized in that: The CNTs are short-chain CNTs and long-chain CNTs, the short-chain CNTs have a length between 0.5 microns and 1 micron, and the long-chain CNTs have a length between 3 microns and 8 microns; the short-chain CNTs are used to bridge the LLZO fine particles and the NCM large particles; the long-chain CNTs are used as a whole to cover the composite NCM large particles, so that the entire composite NCM large particles have better conductivity.
11. The NCM positive electrode particle coated with LLZO and glass phase according to claim 9, characterized in that: The proportion of the total weight of the CNT to the weight of a single composite NCM large particle is between 0.1wt% and 2wt%.
12. The NCM positive electrode particle coated with LLZO and glass phase according to claim 9, characterized in that: It also includes: a plurality of nano-scale amorphous carbons are coated on the outside of the positive electrode particles wrapped with CNTs, forming a positive electrode particle coated with carbon material as a whole, and each of the nano-scale amorphous carbons is mainly located between the gaps formed by the interlacing of a plurality of CNTs.
13. The NCM positive electrode particle coated with LLZO and glass phase according to claim 12, characterized in that: The size of the nano-scale amorphous carbon is 20 nanometers to 100 nanometers.
14. The NCM positive electrode particle coated with LLZO and glass phase according to claim 12, characterized in that: The total weight of the nano-scale amorphous carbon accounts for 0.1wt% to 2wt% of the weight of a single composite NCM large particle; the nano-scale amorphous carbon serves as a conductive agent; and the nano-scale amorphous carbon is distributed in the gaps between the CNTs.
15. The NCM positive electrode particle coated with LLZO and glass phase according to claim 12, characterized in that: The ratio of (the CNT+the nano-scale amorphous carbon):single composite NCM large particle=(0.09-3):100 is the weight ratio.
16. The NCM positive electrode particle coated with LLZO and glass phase according to claim 12, characterized in that: The CNT: the nano-scale amorphous carbon: the single composite NCM large particle = 0.5:1:100, which is a weight ratio.
Citation Information
Patent Citations
Composite positive electrode capable of working at high voltage and preparation method thereof
CN110676447A
Positive electrode of lithium metal battery, lithium metal battery and preparation method of lithium metal battery
CN111834620A
Semi-solid lithium ion battery and preparation method thereof
CN113793976A
Battery positive electrode material and manufacturing method thereof
CN114784247A
Positive electrode material and battery
CN116195085A
Cited By
Positive electrode composite material and electrode plate of lithium ion battery
EP4807797A1
